2020
DOI: 10.35701/rcgs.v22n3.704
|View full text |Cite
|
Sign up to set email alerts
|

Análise Hidrológica Do Igarapé Do Mindu, Manaus, Amazonas, Brasil

Abstract: O objetivo deste artigo é analisar parâmetros hidrológicos no Igarapé do Mindu, localizado na área urbana da cidade de Manaus. Foram calculadas as médias mensais de cota e precipitação para entender a importância de ambas para o regime hidrológico. Realizou-se trabalhos de campo entre os anos de 2018-2019 em seis pontos de análise para calcular a velocidade de fluxo (utilizou-se o método do flutuador), vazão do igarapé e observar influências naturais e antrópicas no canal. O Igarapé do Mindu possui o período d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…In this respect, it is important to note that in the conclusions reported by Queiroz et al (2020) about dams that occur in the Mindú stream, Manaus -Amazonas, in streams that vary throughout the length of this body of water, the author observed that there is variation in the amount of average speed (0.9 m 3 /s to 14.6 m 3 /s).…”
Section: Influences On Flowmentioning
confidence: 96%
See 2 more Smart Citations
“…In this respect, it is important to note that in the conclusions reported by Queiroz et al (2020) about dams that occur in the Mindú stream, Manaus -Amazonas, in streams that vary throughout the length of this body of water, the author observed that there is variation in the amount of average speed (0.9 m 3 /s to 14.6 m 3 /s).…”
Section: Influences On Flowmentioning
confidence: 96%
“…"the volume of water that passes through a given section of a bed in a given time, expressed in m 3 /s (Bonifácio;Freire, 2013;Braga et al, 2015;Carvalho, 2012;Palhares;Rusello;Variano, 2007;Queiroz et al, 2020;Santos et al, 2015;Ferreira, 2019;Tucci, 1997)".…”
Section: Conceptsmentioning
confidence: 99%
See 1 more Smart Citation